Microsoft 365 Fundamental Guide over 100 tips and tricks to help you get up and running with m365 quickly - Moraes, Gustavo (PACKT PUBLISHING LIMITED, 2022)
Become a Microsoft 365 superuser and overcome challenges using the wide range of features offered by Microsoft 365 apps including SharePoint, Teams, Power Automate, Planner, and To-Do Key Features Enhance your productivity with this consolidated guide to using all the tools available in Microsoft 365 Improve your collaboration and maximize efficiency using various M365 features Integrate project, task, and people management within one ecosystem Book Description With its extensive set of tools and features for improving productivity and collaboration, Microsoft 365 is being widely adopted by organizations worldwide. This book will help not only developers but also business people and those working with information to discover tips and tricks for making the most of the apps in the Microsoft 365 suite. The Microsoft 365 Fundamentals Guide is a compendium of best practices and tips to leverage M365 apps for effective collaboration and productivity. You'll find all that you need to work efficiently with the apps in the Microsoft 365 family in this complete, quick-start guide that takes you through the Microsoft 365 apps that you can use for your everyday activities. You'll learn how to boost your personal productivity with Microsoft Delve, MyAnalytics, Outlook, and OneNote. To enhance your communication and collaboration with teams, this book shows you how to make the best use of Microsoft OneDrive, Whiteboard, SharePoint, and Microsoft Teams. You'll also be able to be on top of your tasks and your team's activities, automating routines, forms, and apps with Microsoft Planner, To-Do, Power Automate, Power Apps, and Microsoft Forms. By the end of this book, you'll have understood the purpose of each Microsoft 365 app, when and how to use it, and learned tips and tricks to achieve more with M365. What you will learn Understand your Microsoft 365 apps better Apply best practices to boost your personal productivity Find out how to improve communications and collaboration within your teams Discover how to manage tasks and automate processes Get to know the features of M365 and how to implement them in your daily activities Build an integrated system for clear and effective communication Who this book is for Whether you're new to Microsoft 365 or an existing user looking to explore its wide range of features, you'll find this book helpful. Get started using this introductory guide or use it as a handy reference to explore the features of Microsoft 365. All you need is a basic understanding of computers.